1999
DOI: 10.5144/0256-4947.1999.101
|View full text |Cite
|
Sign up to set email alerts
|

Management Plan of Post-Angiography False Aneurysms of the Groin

Abstract: Background: False aneurysm (FA) of the groin is a potentially serious complication of angiographic procedures. We developed a management plan at St. George's Hospital, and prospectively applied it to 14 consecutive cases over a period of one year. Patients and Methods: This report is a prospective cohort study of post-angiography false aneurysms-. Fourteen patients with groin FA presented to the vascular team between October 1995 and September 1996 (0.2% of 6926 angiographic procedures). Nine of the 14 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The risk factors for development of pseudoaneurysms of femoral artery comprise of obesity, use of thrombolytic agents, antegrade puncture, heavily calcified arteries, repeated multiple punctures and low puncture site [4]. The incidence varies in different reports being as low as 0.8% in large retrospective series [5]. Katzenschlager et al [6], from series of 581 procedures, showed that the incidence of 14% of pseudoaneurysms went down to 1.1%, by the use of a strict protocol of five minute minimal compression time after cessation of bleeding [6].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for development of pseudoaneurysms of femoral artery comprise of obesity, use of thrombolytic agents, antegrade puncture, heavily calcified arteries, repeated multiple punctures and low puncture site [4]. The incidence varies in different reports being as low as 0.8% in large retrospective series [5]. Katzenschlager et al [6], from series of 581 procedures, showed that the incidence of 14% of pseudoaneurysms went down to 1.1%, by the use of a strict protocol of five minute minimal compression time after cessation of bleeding [6].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoaneurysm; pseudoaneurysmcan is a potentially life threatening complication that particularly occurred in the TF approach. Its incidence in the TF approach was about 0.03% to 0.2% [24]. But it seems to be more prevalent in the era of intervention.…”
mentioning
confidence: 98%